2019
DOI: 10.3390/cells8020151
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Parkinson’s Disease Multimodal Complex Treatment in Germany from 2010–2016: Patient Characteristics, Access to Treatment, and Formation of Regional Centers

Abstract: Parkinson’s disease (PD) is currently the world’s fastest-growing neurological disorder. It is characterized by motor and non-motor symptoms which progressively lead to significant clinical impairment, causing a high burden of disease. In addition to pharmacological therapies, various non-pharmacological treatment options are available. A well established and frequently used multiprofessional inpatient treatment concept in Germany is “Parkinson’s disease multimodal complex treatment” (PD-MCT) which involves ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 17 publications
1
39
0
1
Order By: Relevance
“…For inpatient treatment, however, this also means that it does not make sense to increase dosages immediately before discharge because side effects would then occur with a delay at home. Unfortunately, this is exactly what is demanded by health insurance companies and the medical service of the health insurance companies in Germany, namely, the change in medication until the day of discharge, so that the treatment in the PD multimodal complex programme [ 23 ] can be fully billed. The second aspect, the extent to which nonadherent patients are more likely to perceive side effects (or whether side effects due to inadequate medication are more frequent) would have to be examined in further confirmatory studies with larger numbers of cases.…”
Section: Discussionmentioning
confidence: 99%
“…For inpatient treatment, however, this also means that it does not make sense to increase dosages immediately before discharge because side effects would then occur with a delay at home. Unfortunately, this is exactly what is demanded by health insurance companies and the medical service of the health insurance companies in Germany, namely, the change in medication until the day of discharge, so that the treatment in the PD multimodal complex programme [ 23 ] can be fully billed. The second aspect, the extent to which nonadherent patients are more likely to perceive side effects (or whether side effects due to inadequate medication are more frequent) would have to be examined in further confirmatory studies with larger numbers of cases.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective observational study looking at Medicare data-a government-financed health insurance program for the elderly and disabled in the United Stateshighlighted that women are less likely to have specialist (neurologist) care, together with nonwhites [8]. Accordingly, an a posteriori analysis of multiprofessional treatment approach PD-MCT (i.e., "Parkinson's disease multimodal complex treatment") conducted in Germany in the years 2010-2016 and involving pharmacological and nonpharmacological treatment options such a physical therapy, occupational therapy, and speech therapy, revealed that more male than female patients were treated under this program [9]. A recent study covering 7209 patients at 21 centers in the United States, Canada, the Netherlands, and Israel, disclosed that women are also less likely than men to have informal caregiver support (i.e., support from spouse, family or friends).…”
Section: Introductionmentioning
confidence: 99%
“…From a patient's perspective, PANOS strives to address core requirements: according to a Dutch study carried out in compliance with the voice of customer (VoC) approach [17], the following are the most important patient requirements: (1) desire for self-management, (2) better collaboration between healthcare providers, (3) more time for discussing the future, (4) one healthcare provider who can act as a personal case manager, (5) more knowledge of the disease, (6) more support from my pharmacist, (7) increased focus on the needs of my spouse, (8) more contact with other patients, (9) more provision of information and (10) less fragmentation of healthcare. PANOS addresses aspects 1, 3, 5, 8 and 9 by incorporating a structured patient education program according to the self-management concept, aspects 2 and 10 by the establishment of a structured care pathway and aspect 4 by the provision of such a personal case manager.…”
Section: Panos Evaluated By the Dmic And Comparison To Patient And Exmentioning
confidence: 99%
“…PD care in Germany involves a large number of different healthcare providers and is hindered by fragmentation, lack of communication and coordination [6]. Although defined as a standard of care, the access to specialized treatment is highly limited, aggravating imbalances in care access and hampering the efficient delivery of individualized, multiprofessional care [7].…”
Section: Introductionmentioning
confidence: 99%